Deeper eelgrass meadows are refugia from disease and environmental stressors - Graham, Olivia J.; Aoki, Lillian R.; Rappazzo, Brendan; Eisenlord, Morgan; Harvell, C. Drew (Frontiers in Marine Science, 2025)
Eelgrass (Zostera marina) creates valuable, biodiverse habitats worldwide, but is at risk from combined environmental stressors and disease. We surveyed paired intertidal and subtidal meadows for seagrass wasting disease in the San Juan Islands, WA, USA in summers 2017–2019 to determine how disease varied with depth, temperature, and salinity. We expected reduced disease in deeper meadows with more stable environmental conditions compared to shallower, intertidal meadows with greater thermal and salinity variation. Leveraging a machine-learning algorithm to detect and quantify disease, we measured high disease levels and large changes in meadow densities, particularly in the warmer 2018 summer. Daily mean in situ and remote-sensed temperatures captured exposure to warming, though in situ temperatures better identified site-specific, seasonal thermal ranges. Subtidal meadows experienced nearly 14°C cooler maximum in situ temperatures compared to intertidal meadows. Disease severity was 2.24 times greater in shallow, intertidal meadows compared to deeper, subtidal meadows over the 3-year study and 1.39 times greater during the 2018 warming. Thus, some subtidal meadows can serve as valuable refugia against environmental and pathogenic stressors. Lower eelgrass densities were also associated with increased severity, suggesting a link between disease and meadow patchiness. Temperature and salinity were also key predictors of higher disease: prevalence and maximum sea surface temperatures covaried, as did severity and salinity range, suggesting these environmental factors may differentially influence seagrass wasting disease risk and progression. Our work highlights the value of both subtidal eelgrass meadows and sites with more stable environmental conditions as refugia from multiple stressors, which should be considered as differential drivers of disease.